2022
DOI: 10.1038/s41418-022-00966-5
|View full text |Cite
|
Sign up to set email alerts
|

The lipid peroxidation product 4-hydroxynonenal inhibits NLRP3 inflammasome activation and macrophage pyroptosis

Abstract: Pyroptosis is a form of cell death triggered by the innate immune system that has been implicated in the pathogenesis of sepsis and acute lung injury. At the cellular level, pyroptosis is characterized by cell swelling, membrane rupture, and release of inflammatory cytokines, such as IL-1β. However, the role of endogenous lipids in pyroptosis remains underappreciated. We discovered that 4-hydroxynonenal (HNE), a major endogenous product of lipid peroxidation, inhibited pyroptosis and inflammasome activation. H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 85 publications
1
36
0
Order By: Relevance
“…At present, the molecular mechanisms of macrophages leading to ALI by facilitating oxidative stress and inflammatory response are not fully understood [ 18 ]. Our present study indicated that the levels of SPHK2 and NLRP3 inflammasome in PBMCs were positively correlated with the occurrence and development of ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the molecular mechanisms of macrophages leading to ALI by facilitating oxidative stress and inflammatory response are not fully understood [ 18 ]. Our present study indicated that the levels of SPHK2 and NLRP3 inflammasome in PBMCs were positively correlated with the occurrence and development of ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, 4-HNE binds to the sulfhydryl group of intracellular glutathione, which reduces the consumption of glutathione, weakens the intracellular antioxidant capacity, and further aggravates intracellular oxidative stress ( Balogh and Atkins, 2011 ). Moreover, as the end product of lipid peroxidation, 4-HNE can induce the aggregation and activation of macrophages, induce the expression of inflammatory factors, promote the occurrence of inflammation, and aggravate cerebral ischemia injury ( Liu et al, 2020 ; Hsu et al, 2022 ). As the severity of ischemic brain injury is closely related to the recurrence of cerebral infarction, the level of serum 4-HNE may be one of the main mechanisms related to the recurrence of cerebral infarction by affecting the progress of ischemic brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…Pyroptosis, a programmed cell death pathway, is also known as inflammatory caspase-dependent cell death [ 24 ]. Pyroptosis can be triggered by noninfectious stimuli and microbes [ 25 ] and plays central regulatory roles in the progression of numerous diseases, such as ALI [ 26 ], Alzheimer’s disease [ 27 ], tumor [ 28 ], and inflammatory diseases [ 24 ]. We found that EBE contributed to the inhibition of pyroptosis and restoring numbers of living cells in the cells model.…”
Section: Discussionmentioning
confidence: 99%